Publication manual of the American Psychological Association - American Psychological Association (American Psychological Association, 2010)
Includes bibliographical references and index; Writing for the behavioral and social sciences -- Manuscript structure and content -- Writing clearly and concisely -- The mechanics of style -- Displaying results -- Crediting sources -- Reference examples -- The publication process